Factors associated with suicidal phenomena in adolescents: a systematic review of population-based studies. - Evans, E; Hawton, K; Rodham, K (2004)
Suicidal phenomena (suicide attempts, deliberate self-harm, and suicidal plans, threats and thoughts) are common in adolescents. Identification of factors associated with these phenomena could play an important role in the development of school or community-based prevention and intervention programs. In this article, we report the results of a systematic review of the international literature on population-based studies of factors associated with suicidal phenomena in adolescents. These factors encompass psychiatric, psychological, physical, personal, familial and social domains. The quantity of evidence in support of associations between suicidal phenomena and specific factors is compared with the quantity of evidence against such associations. We conclude with a summary of the findings, including identification of new or neglected areas, which require further investigation. Methodological considerations are highlighted and implications of the findings for clinicians and other professionals concerned with prevention of suicidal behavior by adolescents are discussed.